Southeast Asian farmers learn more about CSA practices - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Community leaders and organizers from six Climate-Smart Villages in Southeast Asia learned about climate change adaptation and mitigation in the Philippines. Together with the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) and participants from Climate-Smart Villages (CSVs) in Cambodia, Laos, Vietnam and the Philippines, the International Institute of Rural Reconstruction (IIRR) conducted the 'Training Course on Climate-Smart Agriculture and Participatory Methods, Facilitation and Community Engagement Techniques for Climate Smart Villages in Southeast Asia' between 8-17 September 2015 on IIRR campus in Silang, Cavite, Philippines.